الزكاة ومساهمتها في التخفيف من البطالة وتوسيع قاعدة التشغيل: حالة صندوق الزكاة الجزائري - فلياشي، سامية (الهيئة العالمية للتسويق الإسلامي, 2017)
Islam abhors unemployment and encourages work because it is cosidered as a devotion .Working is a duty of every one able in Islam and prophets are not excluded .Zakat plays an important role in mitigating unemployment directly by giving persons who do not find a job or those who are not able to work a chance to have their own business and to practice their crafts and hobbies by giving them all needed farming machines or useful materials .We may give zakat to those who are in the domain of charity .Either directly, the eight expenses of zakat lead to the increase of consumption as a result ,the demand for labour increases. Zakat funds are new way to expense these funds that some Islamic coutries adopt it to improve their propulsion .Algeria is one of these countries that adopted zakat funds in 2003 to propulse zakat .So we can say that zakat funds in Algeria wil have an effective role in reducing unemployment if we collect all the expected zakat in our country .
Keywords: الزكاة -- صندوق الزكاة الجزائري -- البطالة -- التنمية الاجتماعية